Aboriginal and Torres Strait Islander patients' cancer care pathways in Queensland: Insights from health professionals. (18th November 2021) - de Witt, Audra; Matthews, Veronica; Bailie, Ross; Valery, Patricia C.; Adams, Jon; Garvey, Gail; Martin, Jennifer H.; Cunningham, Frances C.
Abstract: Objective: To identify points for improvements within the health system where Aboriginal and Torres Strait Islander cancer patients may experience a lack of continuity in their cancer care. The optimal care pathway for Aboriginal and Torres Strait Islander people with cancer (OCP) framework was utilised as a tool in this work. Methods: Semi‐structured interviews were conducted with health professionals at the primary health care (PHC) and hospital setting. Data were categorised into six steps using the OCP framework. Results: This study identified multiple time‐points in the cancer pathways that could be strengthened to increase the continuity of cancer care for these patients. In addition, the provision of person‐centred care and adequate education tailored to patients' and health professionals' needs can help minimise the likelihood of patients experiencing a lack of continuity in their cancer care. Participants were recruited from an urban hospital (n = 9) and from six Aboriginal Community Controlled Health Services (n = 17) across geographical locations in Queensland. The provision of culturally competent care, effective communication, coordination and collaboration between services along the cancer pathway from prevention and early diagnosis through to end‐of‐life care were highlighted as important to enhance care continuity for Indigenous Australians. Conclusion: The implementation of recommendations outlined in the OCP framework may help with improving cancer care continuity for Indigenous patients with cancer. Summary: Aboriginal and Torres Strait Islander people can sometimes find cancer care pathways complex and difficult to navigate. This study identified points in the cancer pathways that could be strengthened to increase the continuity of cancer care for these patients which could potentially lead to improved outcomes.